Location of response facilities: a simultaneous game between state and terrorist. (3rd December 2010) - Berman, Oded; Gavious, Arieh; Huang, Rongbing
We study a simultaneous move game with two players: a terrorist and a state where the latter installs facilities that provide support in case of a terrorist attack. While the state installs the facilities such that the metropolitan area attacked is the one that minimises her disutility (i.e. minimises 'loss'), the terrorist, who is not aware of the location of the facilities, attacks one of the metropolitan areas to maximise his utility. An analytic solution for some specific network structure is introduced. Numerically, we solve the problem for a case study of the 20 largest metropolitan areas in the USA.